Left ventricular rotation and right–left ventricular interaction in congenital heart disease: the acute effects of interventional closure of patent arterial ducts and atrial septal defects*. (29th July 2013) - Laser, Kai T.; Haas, Nikolaus A.; Fischer, Markus; Habash, Sheeraz; Degener, Franziska; Prinz, Christian; Körperich, Hermann; Sandica, Eugen; Kececioglu, Deniz
Abstract Background Left ventricular rotation is physiologically affected by acute changes in preload. We investigated the acute effect of preload changes in chronically underloaded and overloaded left ventricles in children with shunt lesions. Methods A total of 15 patients with atrial septal defects (Group A: 7.4 ± 4.7 years, 11 females) and 14 patients with patent arterial ducts (Group B: 2.7 ± 3.1 years, 10 females) were investigated using 2D speckle-tracking echocardiography before and after interventional catheterisation. The rotational parameters of the patient group were compared with those of 29 matched healthy children (Group C). Results Maximal torsion (A: 2.45 ± 0.9°/cm versus C: 1.8 ± 0.8°/cm, p < 0.05), apical peak systolic rotation (A: 12.6 ± 5.7° versus C: 8.7 ± 3.5°, p < 0.05), and the peak diastolic torsion rate (A: −147 ± 48°/second versus C: −110 ± 31°/second, p < 0.05) were elevated in Group A and dropped immediately to normal values after intervention (maximal torsion 1.5 ± 1.1°/cm, p < 0.05, apical peak systolic rotation 7.2 ± 4.1°, p < 0.05, and peak diastolic torsion rate −106 ± 35°/second, p < 0.05). Patients in Group B had decreased maximal torsion (B: 1.8 ± 1.1°/cm versus C: 3.8 ± 1.4°/cm, p < 0.05) and apical peak systolic rotation (B: 8.3 ± 6.1° versus C: 13.9 ± 4.3°, p < 0.05). Defect closure was followed by an increase in maximal torsion (B: 2.7 ± 1.4°/cm, p < 0.05) and the peak diastolic torsion rate (B: −133 ± 66°/second versus −176 ± 84°/second, p < 0.05). Conclusions Patients with chronically underloaded left ventricles compensate with an enhanced apical peak systolic rotation, maximal torsion, and quicker diastolic untwisting to facilitate diastolic filling. In patients with left ventricular dilatation by volume overload, the peak systolic apical rotation and the maximal torsion are decreased. After normalisation of the preload, they immediately return to normal and diastolic untwisting rebounds. These mechanisms are important for understanding the remodelling processes.